Charcot-Marie-Tooth Disease vs Idiopathic: A Comparison of Pes Cavovarus Using Known and Novel Measurements - Eli Schmidt BS; Nolan M. Schonhorst; Andrew Behrens BS; Grayson M. Talaski; Jason Wilken MPT, PhD; Donald D. Anderson PhD; Cesar de Cesar Netto MD, PhD; Bopha Chrea MD (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Hindfoot Introduction/Purpose: Pes cavovarus (PC) is clinically identified as an elevated longitudinal arch. In the setting of Charcot-Marie-Tooth disease this often presents in more severe deformity due to muscular imbalance, however, pes cavus may also present idiopathically. The transverse arch (TA) is thought to play a critical role in foot stiffness and has been applied in progressive collapsing foot deformity (PCFD). This novel approach has never been applied to the pes cavus model. Therefore, the objectives of this study were to evaluate morphological differences in CMT PC and idiopathic PC including recently described measures of the transverse arch. We hypothesize that CMT PC will be more severe than idiopathic PC, as evidenced by preliminary underpowered data, and that CMT PC will have a more pronounced transverse arch. Methods: Weightbearing CT images were retrospectively evaluated in 32 CMT feet with pes cavus (CMT-PC) and 32 idiopathic pes cavus (I-PC) feet. Eleven two-dimensional (2D) measurements and four three-dimensional (3D) measurements were evaluated. Of these, a novel measurement termed the transverse arch plantar (TAP) angle, previously applied in PCFD, was used to assess the TA. (Figure 1a). Other measurements performed in the sagittal plane include calcaneal pitch, talus-first metatarsal angle, cuneiform-to-floor distance, cuneiform-to-skin distance, navicular-to-skin distance and navicular-to-floor distance. Axial measurements included talus first-metatarsal angle (Kite’s angle), and forefoot arch angle. Finally, 3D measurements consisted of foot and ankle offset (FAO), calcaneal offset, and hindfoot alignment angle. Results: Overall, the CMT-PC cohort demonstrated greater deformity for all measures. Specifically, the CMT-PC cohort showed a significantly greater cuneiform-to-floor distance (p=0.018), cuneiform-to-skin distance (p=0.022), Kite’s angle (p < 0.001) and forefoot arch angle (p=0.037) when compared to I-PC (Table 1) (Figure 1 b-c). Assessment of the TA demonstrated that the TAP angle is greater in CMT-PC than in I-PC with a mean angle of mean angle of 93.11° (SD 12.00) compared to 100.81° (SD 9.65) respectively (p=0.006). Patients with CMT-PC also showed a significantly higher TA at all locations measured. This includes a greater distance between the plantar first cuneiform and the plantar second metatarsal (p < 0.001), the first cuneiform and third metatarsal (p=0.005) and the first cuneiform and the fourth metatarsal (p=0.012) (Table 2) Conclusion: To the best of the author’s knowledge, this is the first study to investigate the transverse arch in the pes cavovarus population. The transverse arch as a whole, and each component of the transverse arch, were significantly more affected in CMT-PC than in I-PC. Further, all included measures were greater in CMT-PC than in I-PC including a significantly greater cuneiform height, Kite’s angle and forefoot arch angle. This suggests that not only do these two disease processes differ, but that the transverse arch is implicated in the development of pes cavovarus and should be investigated further. Figure: Two and three dimensional measurements included as well as example images in CMT and idiopathic pes cavus